Rancang Bangun Sistem Informasi Kegiatan Praktek Kerja Industri (Prakerin) Siswa Smk - Syaiful Adli (Syntax Idea)
Technological advancements have significantly impacted various fields, including education. One of the implementations of technology in education is a web-based information system that enhances efficiency and effectiveness in data management. This study aims to design and develop an information system for Industrial Work Practice (Prakerin) activities for students of SMK Negeri 2 Guguak to address inefficiencies in manual data management. The software development method used is the Waterfall approach, consisting of requirement analysis, system design, implementation, testing, and maintenance phases. The system is developed using the Laravel framework based on PHP and features student data management, mentor teachers, company supervisors, and student daily journal reporting. The implementation results show that the developed system facilitates Prakerin management, improves data accuracy, and saves time and costs in the administration process. This information system is expected to provide a more effective solution in supporting Prakerin activities at SMK Negeri 2 Guguak.